Access and availability barriers: emergency clinical laboratory service in public hospitals - Avila-Larreal, Ayari G. (2022)
Objective. To describe the barriers to access and availability in emergency clinical laboratories in two type IV hospitals with different geographical locations in the Zuliana Region. Method. Descriptive and comparative study, with a non-experimental cross-sectional design. Non-probabilistic sampling with a sample size of 290 service users, 80 from Hospital 1 (H1) and 210 from Hospital 2 (H2). The data were obtained through a mixed survey of own elaboration, validated by agreement between experts. Descriptive statistics and comparison of means were used, using the T Student technique at 95% confidence. Results. The main access barrier found was geographical, in H1 (97.5%) and H2 (71.9%). Differences were found in the form of transportation and time required to reach the health center; in H1 the patients used their vehicles (48.8%) with a transfer time of 13.25±4.71 minutes; and in H2 public transport is mainly used (74.3%) with longer transfer time (50.09±34.4 min). The main administrative barrier was the lack of basic supplies (97.5% H1 vs 98.1% H2). There are economic barriers in both health centers: 53.8% in H1 and 56.7% in H2. There was greater availability of tests in the emergency laboratory of H1 (85.6%) than in H2 (31.72%). Conclusion. There are geographical, administrative and economic barriers to access and differences in the availability of supplies between the laboratories of the two hospitals.